Standard Representation of Set Partitions of Γ1 non-deranged permutations - M, Ibrahim; M, Muhammad (International Journal of Computer Sciences and Engineering, 2019)
Some further theoretic properties of the scheme called non-deranged permutation Group, especially in relation to ascent block were identified and studied in this paper. This was done first through some computations on this scheme using prime numbers . A recursion formula for generating maximum number of block and minimum number of block were developed and it’s also observed that is equidistributed with for any arbitrary permutation group and it in decreasing order for non-deranged permutations it also established that the number of ascent block in is.